Intravenous Paracetamol, Morphine, or Ketorolac for theTreatment of Renal Colic: A Randomized Double Blind Clinical Trial - Reza Yazdani (Journal of Research in Medical and Dental Science, 2018)
To determine the analgesic efficacy of intravenous paracetamol versus ketorolac and morphine for the treatment of acute renal colic. This study was a double blind randomized clinical trial that prospectively conducted in emergency department (ED) during September 2012 to August 2013. Totally 150 subjects were randomly assigned in a 1:1:1 ratio to one of the following treatment groups: (1) A single dose of 1 g intravenous paracetamol (apotel) in 100 ml normal saline during 15 min; (2) A single dose of 10 mg intravenous morphine sulfate in 100 ml normal saline during 15 min; (3) A single dose of 30 mg intravenous ketorolac in 100 ml normal saline during 15 min. The severity of pain was measured based on 100 mm visual analogue scale from 0 mm to 100 mm equaling no pain to worst pain , and a verbal 4 points scales of mild, moderate, sever and very sever, respectively, just before intervention and 30 minutes after that.The pain intensity score was 36.13 ± 27.64 Visual analogue 30 min after intervention, pain score decreased significantly within 30 min compared to baseline pain intensity (P < 0.001). The most frequent adverse effect among the participants was dry mouth, which was more seen in morphine group.Similar efficacies were obtained for three medications, which were used in current study. However, the results suggested that comparing to morphine and ketorolac, paracetamol had lower complications.